ANALISIS KUALITAS PRODUK, KUALITAS PELAYANAN, KONDISI EMOSIONAL, PERSEPSI HARGA DAN BIAYA TERHADAP KEPUASAN PESERTA JKN-KIS PEKERJA PENERIMA UPAH BADAN USAHA SWASTA DI BPJS KESEHATAN CABANG SAMPIT KALIMANTAN TENGAH - Adi Suci Guntoro (JURNAL KINDAI, 2020)
This research was conducted to determine the effect of product quality, service quality, emotional conditions, price perceptions and costs on JKN-KIS participant registration satisfaction of workers receiving wages private businesses entity in Healthcare Social Security Agency, Sampit Branch, Central Borneo. This study uses questionnaire to 100 workers receiving wages private businesses entity. The results showed that variables of product quality, service quality and price perception has significant effect on satisfaction of JKN-KIS participants workers receiving wages private businesses entity. Meanwhile, emotional condition and cost variables hasn’t significant effect on satisfaction of JKN-KIS participants workers receiving wages from private businesses entity. Then, variables of product quality, service quality, emotional condition, perceived price and cost simultaneously has significant effect satisfaction of JKN-KIS participants workers receiving wages private businesses entity with calculated F value (4.082) > F table (2.310). Based on the results of study it’s also known that service quality is the most variable has significant effect on satisfaction of JKN-KIS participants workers receiving wages private businesses entity with value of Beta Coefficients 0.196. Keywords: JKN-KIS, product quality, service quality, emotional condition, price perception, cost, satisfaction